Strategi Promosi Digital Partisipatif: Revitalisasi Branding Wisata Budaya Kampung Jawi Kota Semarang - Faisal Yusuf; Herman Paninggiran; Muchammad Wibowo; Almas Imanina; Kefas Harnanto (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2025)
Kampung Jawi, a cultural tourism destination in Semarang City, has experienced a significant decline in tourist visits due to stagnant digital promotion activities. The main problem lies in the absence of an integrative and empirically tested model that combines technology, community empowerment, and cultural reinforcement for Indonesian cultural tourism villages. This study aims to address this gap by formulating and testing the participatory SOME+ model, a modification of the original SOME framework (Share, Optimize, Manage, Engage) with the addition of TRAIN (capacity building) and SUSTAIN (sustainability). Using a mixed-methods exploratory sequential design (QUAL → quan), data were collected through observation, in-depth interviews, focus group discussions (FGDs), and social media content analysis. The findings highlight initial challenges such as low digital literacy and fragmented coordination. Nevertheless, a two-week pilot project increased social media engagement rates from 2.8% to 4.3% (a 52% rise) and enhanced community participation in content production from 25% to 41% (a 64% rise). The synthesis of these findings indicates that the SOME+ model effectively revitalizes the digital branding of cultural tourism villages. This research concludes that the participatory SOME+ model is a practical and replicable framework for strengthening community-based digital promotion and is recommended for adoption in rural tourism development policies.